Developing local currency bond markets in Asia - Cyn-young Park (Asian Development Bank (ADB), 2016)
Local currency bond markets in emerging Asian economies have expanded dramatically since governments took steps to end the currency and maturity mismatches that savaged borrowers in the region's financial crisis nearly 20 years ago. Encouraged in part by regional cooperation programs such as the Asian Bond Markets Initiative, the value of local currency government and corporate bond sales has grown fourfold in the past decade, helping to fund much-needed infrastructure development and protect businesses from global financial shocks. However, much more needs to be done to strengthen market infrastructure and institutions, address inconsistent policies and regulations, and enhance corporate governance. This paper presents evidence that better macroeconomic performance and stronger institutions help develop larger local currency bond markets and also create conditions for the growth in local currency sales of corporate debt and bonds with longer maturities. Regional integration can be stepped up to support the key determinants for developing efficient local currency bond markets in emerging Asia.
Keywords: G10; G11; G18; 330; bond market; financial integration; local currency bonds